Methyl Violet Dye as Corrosion Inhibitor for Carbon Steel in Acidic Medium" - Hamida Edan Salman (Journal of Global Pharma Technology, 2016)
The present work involves study the Methyl Violet dye as a corrosion inhibitor with concentrations rang (25- 200) ppm for their influence on carbon steel corrosion in 1M H2SO4 at temperature range (303-323) K utilize"potentiodynamic polarization technique."Corrosion rates, Corrosion potential, current corrosion, inhibition efficiency, cathodic and anodic Tafel islopes were found."The study also examined influence of concentration and temperature on inhibition efficiency the results manifest that the dye utilized could be good and active inhibitor for carbon steel. Thus, the dwindle in the rate of corrosion is due to the of forming of a protective strata formed on the surface electode that which adsorbed physically and chemically on the surface of carbon steel. Energy values of activation (Ea), enthalpy (ΔH*), energies of Gibbs (ΔG*), and activation entropy (ΔS*), alongside along"thermodynamic amounts of corrosion and adsorption provision indicating the dye effect as a good inhibitor. The isotherm langmuir paradigm be obvious shaped well to enhanced the adsorption operation on carbon steel surface in acidic solution.